Choques petroleros y política monetaria : análisis de un modelo DSGE para la economía colombiana (2017)
"Sudden changes in oil prices pose a challenge in the implementation of monetary policy for countries economically dependent on the oil industry, as is the case of Colombia. From a dynamic stochastic general equilibrium model (DSGE) standpoint, this paper analyzes the effects of a transitory oil price shock on the Colombian economy." -- Tomado del Formato de Documento de Grado.